تقارب عقائد کے لئے علمائے اہل سنت کی کاوشیں (ایک تحقیقی و تجزیاتی مطالعہ): The Efforts of Ahl al-Sunnah Scholars for Convergence of Beliefs (An Exploratory and Analytical Study) - Hussain, Tajamal; Mahmood, Dr. Muhammad Rizwan (Al-Amīr Research Journal for Islamic Studies, 2022)
There are many beliefs in the sects that are common, while the differences are very small and minor. The differences are usually of a sectarian, ijtihad and preferential nature. But the false powers are using these sectarian differences to spread extremist thinking, which is a poison for the Muslim Ummah. Closeness is essential for the survival of the Muslim faith. This unity should not be temporary but should be a message of intellectual and spiritual, material well-being, spiritual maturity and evolution of mental development and unity should be universal. No matter how much the two groups disagree, there are many commonalities. It is important for convergent beliefs to cultivate commonalities rather than divisive ones. So that the atmosphere of hatred is reduced and an atmosphere of unity is created. The history of Islam bears witness to the fact that the Imams, jurists, narrators and commentators have differed on a number of issues. Despite this difference, love, goodwill, brotherhood and unity prevailed. For such interfaith tolerance and harmony, mutual respect is also necessary. Key words: Convergence of beliefs, Unity and solidarity, Interdisciplinary, Shared, Sub-differences, Universal